TEKANAN KERJA DAN STRATEGI KERJA YAKULT LADY DI KOTA PEKANBARU PADA MASA PANDEMI COVID-19 - Johannes Hasibuan; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is entitled "Work Pressure and Work Strategy of Yakult Lady in Pekanbaru City During the Covid-19 Pandemic.” The researcher is very interested in setting this topic because of the importance of work strategies in dealing with work pressure during the Covid-19 pandemic for Yakult Lady. This research is using descriptive quantities method for the data analysis, which concerns the work strategy of Yakult Lady in dealing with work pressure which will then be analyzed using strategy theory. The formulation of the problems in this study are: (1) what is the work pressure of Yakult Lady during the Covid-19 pandemic in Pekanbaru? (2) How is Yakult Lady's work strategy to deal with work pressure during the Covid-19 pandemic in Pekanbaru? The data collection techniques in this study were in the form of questionnaires and documentation. As for the population and samples using the Slovin technique, from 104 populations, 52 samples were obtained and from the research we can see that the Yakult Lady's work strategies are active, passive, and network work strategies are in the high category. Meanwhile, the work pressure of Yakult Lady is in the high category. Keywords: Work Pressure, Yakult Lady, Covid-19 Pandemic, Work Strategy